Using Literature to create Awareness of Domestic Violence for Secondary School Students - Zachariah, Tirzah Zubeidah; Kudus, Nazima Versay; Izahar, Mustafa (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2023)
Some 7468 domestic violence cases were reported in 2021, which was an increase of 42% from 5260 cases in 2020, as stated by the Malaysian Ministry of Women, Family, and Community Development. This informs us that this type of violence is becoming more rampant every year. As such, as educators and teachers, we must help to create awareness of domestic violence among our students. This paper aims to explore strategies for teaching the topic and also present the challenges that may emerge in the classroom. This paper will also focus on the importance of raising awareness about domestic violence among secondary school students.